Rethinking fieldwork: researching food in the aftermath of lockdown - Diana Mihuț; Otilia Hedeșan (Swedish Journal of Romanian Studies, 2024)
The article raises questions related to field research methodology in a specific context. The authors take into consideration mainly the context of uncertainty, generated by Covid-19 pandemics which forced them to reshape the field research methodology as previously known and commonly used by Romanian ethnologists. The authors provide a brief presentation and analysis of the first steps done as part of what later would become a larger field experience in terms of investigating Romanian food heritage. It relies on five examples represented by five interviews conducted during the Covid-19 pandemic. The interviews that compose the case study have a special value. The negotiation to set up the meetings, the arguments of each of the parties, the conditions in which the discussions were organized are all angles that deserve to be discussed as source of what we might call ethnological motivation. What can determine the people, members of a specific culture, to share their knowledge and their life experience about a certain topic, when the very act of speaking might be a dangerous one? In each of these examples, the informant was responsive when informed that we were conducting research related to local traditions, specific family cuisine, without producing television shows, and without overexposing themselves. We notice the existence of a need to tell, a real duty to tell relevant information about one’s own culture, a vector that characterizes communities just as, for the researcher, there is a work ethic which implies his obligation to make all necessary efforts to find out information.